PERANCANGAN KEMASAN KOPI BERINGIN DI NAGARI ALAHAN PANJANG, KECAMATAN LEMBAH GUMANTI, KABUPATEN SOLOK - REZKI RAMADHANI, Dr. Syafwandi, M.Si., Dini Faisal, M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2015)
Effort "Kopi Beringin" is one of the coffee powder products in Nagari Alahan Panjang, District Lembah Gumanti, Kab. Solok, established in 1985 under the leadership of Zulfa Hendra. Weakness of these products contained in the package wrapped in clear plastic, packaging as it can not compete in the market. The author aims to design packaging design Kopi Beringin order to compete in the market, especially in young people.The design of the packaging is shaped sheath, made from calico cloth, string ties as a binder cover, hanger tape as product information. Layout product logos, illustrations effort "Kopi Beringin" with the concept of urban art that aims to attract the attention of young people to buy their products and provide headline "Fragrant and Delicious", the tagline "100% Genuine Coffee" will reinforce the views and information about the product delivered invitation packing.Packaging design as a communication tool can be interpreted that the packaging design not only as a wrap or cover an item or group of items, but provide information that is clear and complete for the content or the content of a product, ideally when the packaging design is able to provide information to consumers value will it is better to avoid consumer confusion.Proper design method is the SWOT analysis as in the design of the writer redesigning existing packaging designs, with a balance of strengths, weaknesses, opportunities, and threats that a comparison between the new designs, old designs and competitors products.Keywords: Design packaging, Kopi Beringin, Urban Art